Determinants of Antenatal Care Visit Compliance among Pregnant Women in Kualuh Hulu District, North Labuhanbatu Regency - Nova Larysca Manik; Ermi Girsang; Sri Lestari Ramadhani Nasution (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Background: Antenatal care (ANC) is a core strategy for reducing maternal and neonatal mortality through early detection and management of pregnancy complications. However, ANC coverage in Kualuh Hulu District, North Labuhanbatu Regency, remains suboptimal, with fluctuating maternal and infant death rates signaling persistent service gaps. Identifying the local determinants of ANC compliance is essential for designing targeted interventions. Methods: A cross-sectional study was conducted among 153 second- and third-trimester pregnant women recruited through total sampling from four public health centers in Kualuh Hulu District. Data were collected using a structured, validated questionnaire. Analysis included univariate description, bivariate analysis using Chi-square tests, and multivariate binary logistic regression to identify independent determinants. Results: High ANC compliance was observed in 65.4% of participants. Bivariate analysis showed significant associations with six factors: knowledge (p<0.001; OR=4.97), attitude (p<0.001; OR=7.52), decision-making autonomy (p<0.001; OR=6.01), perceived service quality (p=0.002; OR=3.89), availability of staff and facilities (p=0.014; OR=2.90), and transportation and examination costs (p=0.006; OR=2.36). After multivariate adjustment, only knowledge (AOR=5.25; 95% CI: 2.17–12.68), attitude (AOR=4.38; 95% CI: 1.72–11.12), and decision-making autonomy (AOR=4.57; 95% CI: 1.87–11.16) remained significant independent predictors. Conclusions: Knowledge, attitude, and decision-making autonomy are the dominant determinants of ANC compliance in this rural setting. Interventions should prioritize continuous health education, awareness-building counseling, and empowerment of women in health-related decisions, while service quality improvements and cost support serve as essential enabling factors.